2012
DOI: 10.1002/adv.21321
|View full text |Cite
|
Sign up to set email alerts
|

Polypyrrole/Poly(acrylonitrile‐co‐butyl acrylate) Composite

Abstract: Poly(acrylonitrile-co-butyl acrylate) [P(AN-co-BuA)] was synthesized from acrylonitrile (AN) 95% and butyl acrylate (BuA) 5%-molar ratios-by free-radical polymerization in aqueous media, using ceric ammonium nitrate as an initiator. Pyrrole was oxidatively polymerized in dimethylformamide in the presence of P(AN-co-BuA) matrix to produce polypyrrole (PPy) composites. Composite thin films were produced by solution casting onto smooth glass surfaces. Scanning electron microscopy and Fourier transform infrared-at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…The flow rate of the feed was set at 1 mL/h, and the applied voltage between the tip and collector was set to 16 kV, with a tip‐to‐collector distance of 16 cm. The fibers were collected on the aluminum foil in the form of nonwoven fabric . A schematic illustration of the experimental apparatus is shown in Figure .…”
Section: Methodsmentioning
confidence: 98%
See 1 more Smart Citation
“…The flow rate of the feed was set at 1 mL/h, and the applied voltage between the tip and collector was set to 16 kV, with a tip‐to‐collector distance of 16 cm. The fibers were collected on the aluminum foil in the form of nonwoven fabric . A schematic illustration of the experimental apparatus is shown in Figure .…”
Section: Methodsmentioning
confidence: 98%
“…The fibers were collected on the aluminum foil in the form of nonwoven fabric. 39 A schematic illustration of the experimental apparatus is shown in Figure 1.…”
Section: Methodsmentioning
confidence: 99%
“…Copolymerization of AN gives the chance of distruption of strong dipole interactions, increasing decomposition temperature and decreasing high melting point of the polymer [6]. Acrylates (methyl acrylate and butyl acrylate), vinyl acetate, ketones, alcohols, acrylic acid and itaconic acid (IA) are among the widely used comonomers [7][8][9][10][11][12]. Polymerization of AN with vinylacetate was studied by Çetiner et al [6] and it was observed that by addition of vinylacetate to AN, the solubility of the polymer in spinning solutions increased.…”
Section: Introductionmentioning
confidence: 99%
“…Sen and Sarac [13] selected IA as a comonomer for the production of poly(acrylonitrile-co-itaconic acid) (P(AN-co-IA)) polymer, and they showed that using higher IA ratios in polymerization step let to decreased decomposition temperature of the obtained polymer. In a study, Unsal et al [10] copolymerized AN with butylacrylate and pyrrole; they showed that by incorporation of butylacrylate to the system, the mechanical properties of the resulting polymer improved. Copolymerization of P(AN-co-IA)-polypyrrole was achieved by Arman and Sarac [14] via emulsion polymerization for the synthesis of AN and vinylacetate in order to investigate the morphology of the nanocomposites.…”
Section: Introductionmentioning
confidence: 99%
“…They are also suitable for a wide range of applications such as supercapacitors, dye‐sensitized solar cells, fuel cells, rechargeable lithium batteries, sensors, and drug‐carrying material because of colloidal stability, low cost, and ease of preparation . Hydrogel conductivity can be improved by the addition of carbon‐based particles and using conducting organic comonomers . Graphene among carbon‐based materials seems to have exceptional thermal, mechanical, and electrical properties …”
Section: Introductionmentioning
confidence: 99%